A Large‐scale, Rapid Public Health Response to Rabies in an Organ Recipient and the Previously Undiagnosed Organ Donor. (27th March 2014) - Wallace, R. M.; Stanek, D.; Griese, S.; Krulak, D.; Vora, N. M.; Pacha, L.; Kan, V.; Said, M.; Williams, C.; Burgess, T. H.; Clausen, S. S.; Austin, C.; et al.
Summary This article describes and contrasts the public health response to two human rabies cases: one organ recipient diagnosed within days of symptom onset and the transplant donor who was diagnosed 18 months post‐symptom onset. In response to an organ‐transplant‐related rabies case diagnosed in 2013, organ donor and recipient investigations were conducted by multiple public health agencies. Persons with potential exposure to infectious patient materials were assessed for rabies virus exposure. An exposure investigation was conducted to determine the source of the organ donor's infection. Over 100 persons from more than 20 agencies spent over 2700 h conducting contact investigations in healthcare, military and community settings. The 564 persons assessed include 417 healthcare workers [5.8% recommended for post‐exposure prophylaxis (PEP)], 96 community contacts (15.6% recommended for PEP), 30 autopsy personnel (50% recommended for PEP), and 21 other persons (4.8% recommended for PEP). Donor contacts represented 188 assessed with 20.2% recommended for PEP, compared with 5.6% of 306 recipient contacts recommended for PEP. Human rabies cases result in substantial use of public health and medical resources, especially when diagnosis is delayed. Although rare, clinicians should consider rabies in cases of encephalitis of unexplained aetiology, particularly for cases that may result in organ donation.